2008
DOI: 10.1139/g08-066
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome organization and phylogeny of two vespid wasps

Abstract: We sequenced the entire mitochondrial genome of Abispa ephippium (Hymenoptera: Vespoidea: Vespidae: Eumeninae) and most of the mitochondrial genome of Polistes humilis synoecus (Hymenoptera: Vespoidea: Vespidae: Polistinae). The arrangement of genes differed between the two genomes and also differed slightly from that inferred to be ancestral for the Hymenoptera. The genome organization for both vespids is different from that of all other mitochondrial genomes previously reported. A number of tRNA gene rearran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 68 publications
(53 reference statements)
2
70
2
Order By: Relevance
“…This difference could be explained by deletions of tandem sections in the POR, which has been reported in other insects (De Ré et al, 2014;Elbrecht et al, 2013). Nevertheless, a more plausible explanation for this result is the apparent difficulty of the 454 sequencing approach to recover the mitochondrial control region in insects, basically due to the presence of complex repeats that are difficult to sequence and/or assemble (Cameron et al, 2008;Mao et al, 2012;Ramakodi et al, 2014).…”
Section: Mitogenome Architecture Of Aegorhinus Superciliosusmentioning
confidence: 90%
“…This difference could be explained by deletions of tandem sections in the POR, which has been reported in other insects (De Ré et al, 2014;Elbrecht et al, 2013). Nevertheless, a more plausible explanation for this result is the apparent difficulty of the 454 sequencing approach to recover the mitochondrial control region in insects, basically due to the presence of complex repeats that are difficult to sequence and/or assemble (Cameron et al, 2008;Mao et al, 2012;Ramakodi et al, 2014).…”
Section: Mitogenome Architecture Of Aegorhinus Superciliosusmentioning
confidence: 90%
“…Based on these records,~1000 bases of the control region were not part of the assemblies for either taxon. However, the difficulties of sequencing and assembling the mitochondrial control region of insects have long been known [40,41] and the potential drawbacks of our method in this area are discussed below. That being said, all other aspects of genome organization, gene arrangements and gene lengths of C. hominivorax and H. irritans 454-based assemblies are the same as in the previously published versions.…”
Section: Hominivorax and H Irritans Mtgenome Assemblies Versus Prmentioning
confidence: 99%
“…The alignment parameters were the default settings for all genes. The Clustal W alignment parameters were as specified in Cameron et al (2008). The MUSCLE alignment parameters for the rRNA genes were gap open penalty = -400, gap extend penalty = 0; and for the protein-coding genes were gap open penalty = -2.9, gap extend penalty = 0.…”
Section: Sequence Alignmentmentioning
confidence: 99%
“…For example, the monophyly of the Proctotrupomorpha (sensu Rasnitsyn 1988) is well supported by recent studies, but the relationships among the proctotrupomorph families are still controversial (Dowton and Austin 2001;Rasnitsyn and Zhang 2010;Heraty et al 2011). Several analyses have demonstrated that the whole mt genome is a useful tool to resolve hymenopteran evolutionary relationships (Castro and Dowton 2007;Cameron et al 2008;Dowton et al 2009a;Wei et al 2010a). To date, 18 complete mt genomes and 15 nearly complete mt genomes have been successfully sequenced in the Hymenoptera, with 18 taxa added in the last 3 years.…”
Section: Introductionmentioning
confidence: 99%